The given expression can be simplified to: x-12y
If you mean: 13x+2y-10x-7y then it is an algebraic expression that can be simplified to 3x-5y
8y + 7y = 15ySo [ 8y + 9 + 7y ] = 15y + 9If you want to get fancy and factor that expression, it's 3(5y + 3) .
Yes it is.
It cannot be simplified any further, so it is: 2x + 7y
7y + 4 - 4 - 9 = 7y - 9
It can be simplified to: 3+y
4X2+X3+3X+7Y+2X3 can only be simplified to 3X3+4X2+3X+7Y, because X3 and 2X3 are the only like terms.
4x + 3y - 2x - 7y2x - 4y
The given expressions can be simplified to: 7y-8x-14
5y explanaition 5x-5x=0, 0-2y=-2y, -2y+7y=5y
It is: 3y-6
Without an inequality sign it is not an inequality equation but the given expression can be simplified to: 8x-16-7y
If you mean: 3y^2-7y+3-5y+3-4y^2 then it is simplified to -y^2-12y+6
Splitting the equation up into the two variables: x + 4x = 5x -7y + -2y = -9y Therefore, the simplified version is: 5x - 9y
It is simply: 7y+46 or 7y-46
a + 7y
A mathematical expression does not have an answer, if it is algebraic and all of the terms are unlike. For example, x+7y does not have an answer because there are no definite solutions, and there is no possibility to combine like terms. However, the expression 2x+7y+3x does have an answer, but the solution is merely the combination of like terms. (5x+7y)
16+7y-8 = 7y+16-8 = 7y+8
3(10x + y) + 2x + 7y (multiply the 3 through the parentheses then combine like terms) = 30x + 3y + 2x + 7y = 32x + 10 y Evaluate an expression for some values of x and y, means to substitute those values into the expression, such that when x = 3 and y = 1 the value of the given expression is 106: 32x + 10y = 32(3) + 10(1) = 96 + 10 = 106
(4x2)+ (28xy) + (49y2) = (2x + 7y)(2x + 7y) = (2x + 7y)2
-7y + 4y = -3y